Assessing equity in healthcare utilisation in Malaysia / Mohd Ridzwan Shahari - Mohd Ridzwan, Shahari (2016)

(untitled)
Malaysia has made a huge improvement in health over the past several decades, which is supported by continuous government investment in healthcare delivery network. However, the rapid development of Malaysia‟s economy since 1950, has witnessed great changes in demographic structure and the epidemiological pattern of diseases in its population. Moreover, since independence the increasing role of the private health sector has turned Malaysia‟s health system into a dichotomous health delivery system hence the overall country's health system landscape. This study was conducted to assess fairness in healthcare utilisation and its contribution towards universal health coverage in Malaysia. A study on fairness for the healthcare utilisation is driven by the concerns about the impact of welfare, especially among poor. This study covered two main components of healthcare utilisations which are the out-patient and in-patient care services. Assessing the fairness in healthcare utilisation for healthcare services is based on the notion that utilisation for healthcare services must be based on health needs and not been influenced by other factors such as socio-economic background or geographical location of residence. This study analysed the extent of fairness in healthcare utilisation using three sets of Household Health Survey data- National Health and Morbidity Survey (II), (III) and (IV) which allowed the evaluation to be conducted at three points in time, namely, 1996, 2006 and 2011. In addition to assessment of healthcare utilisation at the national levels, these data sets also allowed for sub-national assessment namely by strata, region, state and ownership of government and private facilities. In general, this study revealed that the utilisation for both the out-patient and in-patient care services were equitable. Individuals in this country have been found to have an adequate access for both in-patient and out-patient care services. Secondly, the utilisation of both services were equally distributed across the income-gradient and the utilisation of both services after standardising for the health needs were equally distributed across the income- gradient, regardless of different places of residence, despite growth and increased role of private health sectors, over time. The public facilities were utilised mainly by the poor in rural areas and East Malaysia, meanwhile for private sectors, it is used by the rich particularly in urban areas and peninsular region of Malaysia. This study provides two main policy implications. The first is that equity in healthcare utilisation can be achieved by a system dominated by the public services, in which the provision of comprehensive services by the government will ensure that all segments of the population regardless of their socio-economic background and location of residence, receive adequate health services based on their health needs. The second implication is that the rapid growth of private health sector over time may not necessarily affects the equity status in healthcare utilisation, provided a comprehensively low priced public health services is available throughout the country, to ensure access for the disadvantaged population.